Live audience responses to live televised election debates: time series analysis of issue salience and party salience on audience behavior. Issue 10 (2nd October 2016) - Vergeer, Maurice; Franses, Philip Hans
ABSTRACT: Televised political debates are the platforms for party leaders to outline their party's political programs and to attack those of their political opponents. At the same time journalists who moderate the debates are testing the party leaders' ability to clearly outline and defend their programs. Television audiences of election debates evaluate these party leaders and political parties based on their television performances. Prior to the social media era, viewers' evaluations were collected through phone surveys or web questionnaires. Nowadays viewers share their opinions in real-time on social media. Particularly Twitter is used in the Netherlands as the platform to share these opinions. In this study tweets produced by the audiences of five different televised debates that took place during the campaign for the Dutch 2012 parliamentary elections are analyzed in terms of tweeting about politicians and parties as well as political issues, as well as the content of the debates. This allowed us, using time series analysis, to test the relation between issue salience in debates and issue salience of the audience on Twitter. The issues of 'Employment and income' and 'Europe' were the most tweeted about, roughly aligning with the attention these issues received in televised debates. Findings further show there are consistent audience reactions to issues discussed in the debates: issues of 'Housing', 'Care for the needy', and 'Europe' showing the strongest effects. However, candidates and parties are not explicitly associated by people active on Twitter when certain political issues are being debated on TV.